Respuesta :

Answer:

{4 + 2√3, 4 - 2√3} thus the solution is A.  x = 4 + 2 sqrt(3) or x = 4 - 2 sqrt(3)

Step-by-step explanation:

Solve for x over the real numbers:

(x - 4)^2 = 12

Take the square root of both sides:

x - 4 = 2 sqrt(3) or x - 4 = -2 sqrt(3)

Add 4 to both sides:

x = 4 + 2 sqrt(3) or x - 4 = -2 sqrt(3)

Add 4 to both sides:

Answer: x = 4 + 2 sqrt(3) or x = 4 - 2 sqrt(3)

Answer:

{4 + 2√3, 4 - 2√3} thus the solution is A.  x = 4 + 2 sqrt(3) or x = 4 - 2 sqrt(3)

Step-by-step explanation:

Solve for x over the real numbers:

(x - 4)^2 = 12

Take the square root of both sides:

x - 4 = 2 sqrt(3) or x - 4 = -2 sqrt(3)

Add 4 to both sides:

x = 4 + 2 sqrt(3) or x - 4 = -2 sqrt(3)

Add 4 to both sides:

Answer: x = 4 + 2 sqrt(3) or x = 4 - 2 sqrt(3)